TEORI MEDAN MAKNA DAN KONTEKSTUALITAS HUKUM ISLAM KONTEMPORER: REINTERPRETASI HADIS-HADIS ETIKA EKONOMI ISLAM DALAM WACANA SEMANTIK - Wahyu Hanafi, Nafi'ah, (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2019)
This study aims to describe the actualization of semantic field theory in the reinterpretation of the hadiths of Islamic economic ethics. This research uses descriptive interpretive method. Actualization of semantic field theory can be explained when want to know the meaning of a word then must know the meaning of the word associated with the previous word. If viewed from the nature of the semantic relationship, then the words are grouped into a semantic field divided into 1). sintagmatic 2). set field (paradigmatic). The results of this study explain 1). Hadiths about Islamic economic ethics narrated by Ahmad and Abu Dawud with the word focus "syafā'at". contains the meaning of "mediator of goodness". The meaning of this "intermediary of goodness" is obtained through the formulation of the syntagmatic field, namely to comprehend a series of semantically interconnected words such as "double and rescue" meaning. Semantically terminology, the meaning of the word hadith is "Whosoever intercedes for a good to his brother, then he is rewarded and received, then he has come to a great door of the doors of usury. 2). Hadith about Islamic economic ethics narrated by Muslims. The word focus of the hadith is the word "gharar" which is semantically interpreted by "deception". The meaning of "deception" is obtained through the formulation of the syntagmatic field, namely by understanding the meaning of words that are still relevant to the word "deception", such as the word "unclear, and syubhat". In semantic terms, the meaning of the hadith is "Rasulullah Saw forbade buying by throwing stones and buying fraud. 3). Hadiths about Islamic economic ethics that Bukhori maintains. The focus word of the hadith is "Najsyi" which is semantically interpreted as "deceiving". The meaning of "deceiving" is derived from the paradigmatic field formulation, ie by understanding the relationship between elements at a certain level and other language elements such as "unclean, dirty, and disease" meaning. In semantic terms, the meaning of the hadith is "That the Messenger of Allah forbade buying by way of deceiving".